ADHERENCE TO OTC DIRECTORY -THE PERCEPTION OF COMMUNITY PHARMACISTS IN SAUDI ARABIA - Al-Rukban, Mohammed Othman; Khalil, Mohammad Adnan (Journal of Ayub Medical College Abbottabad, 2012)
Background: Worldwide Ministries of Health (MoH) are encouraged to publish an updated Overthe-Counter (OTC)-Directory that pharmacists should adhere to in dispensing non-prescription medications. The Saudi Ministry of Health has published the OTC-Directory in the year 2000, and since then, it was readily available to all practicing pharmacists at no cost. This study was aimed to investigate the knowledge of practicing pharmacists in Riyadh, Saudi Arabia, regarding permitted self-prescription medications (i.e., OTC-Directory), as well as pharmacists professional competence and adherence at dispensing OTC drugs without prescription. Methods: The study was cross-sectional by design. A computer generated list of simple random sampling was used to select the pharmacies out of 1,500 working in Riyadh. The data was collected from 384 randomly selected community pharmacies by questionnaire using direct investigation method and the total respondents were 405. Associations between qualitative variables were observed using Pearson Chi-square and Fisher Exact test. Results: Four hundred and five (405) pharmacists participated in the survey of which 100% were males and 362 (89.4%) were below the age of 40 years. Majority of them (361, 88.9%) were holding bachelors degree. Almost one-third of the respondents (123, 30.4%) were not aware of the existence of the Saudi OTC-Directory. The pharmacists' geographical location, nationality and attendance of CME activity had significant association with knowledge about the OTC-directory (p<0.05). Two hundred and eighty-two (69.6%) of the pharmacists who had knowledge about Saudi OTC-directory did not comply with its guidelines. Pharmacists with higher degrees were more observant of the OTC-Directory as compared to those with diploma and Bachelor Degree (p=0.014). Conclusions: There is significant non-compliance of OTC-directory by the community pharmacists while providing non-prescription drugs in Riyadh, Saudi Arabia. Keywords: Self medication, OTC-Directory, community pharmacist, pharmacy practice